Pemanfaatan Argumen dalam Teks Diskusi pada BSE Bahasa Indonesia Kelas IX SMP: Media Pengembangan Kreativitas - Anggraini, Dwi; Syafi'i, Imam (Universitas Hamzanwadi, 2021)
This study aims to determine the use of the arguments contained in the discussion text in the BSE Indonesian Language textbook for class IX SMP, both in supporting and challenging arguments. This study uses a qualitative descriptive approach with content analysis method. Sources of data in this study are a number of discussion texts contained in the discussion text material in the BSE Indonesian Language textbook for class XI SMP. The results of this study indicate that the supporting and challenging arguments in the discussion text 1 under the title